The Antiallergic Potential of Quercetin Compared With Dexamethasone and Prednisolone against Histamine H1 Receptors in Vernal Keratoconjunctivitis - Nugraha Wahyu Cahyana; Ulfa Elfiah; Heni Fatmawati (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2024)
Vernal keratoconjunctivitis is an ophthalmological condition that presents significant challenges, especially in children and adolescents, due to chronic inflammation of the conjunctiva and cornea. This inflammation leads to distressing symptoms such as itching, irritation, and photophobia, which severely impact the quality of life. Traditional treatments for this condition often involve antiallergic medications like dexamethasone, prednisolone, and quercetin. However, understanding the precise mechanisms and comparative effectiveness of these treatments is crucial for improving therapeutic outcomes. In this study, protein structure data for dexamethasone (4UDA), prednisolone (8CC1), and quercetin (1JUH) were sourced from the Protein Data Bank (PDB). The crystal structure of the Histamine H1 Receptor (8X5X) was also retrieved from PDB. In silico modeling was carried out using the Cluspro web server to simulate the interactions between these drugs and the receptor. The analysis revealed that quercetin exhibited the lowest Weighted Score of -1810 in cluster 2, outperforming dexamethasone (-1223) and prednisolone (-1372.4), indicating a higher binding potency to the Histamine H1 Receptor. These findings suggest that quercetin has superior potential compared to dexamethasone and prednisolone for binding to Histamine H1 Receptors in the context of vernal keratoconjunctivitis.